Generation of site-specific ubiquitinated histones through chemical ligation and characterization of histone deubiquitinases - Al-Afaleq, Nouf Omar, author; Yao, Tingting, advisor; Cohen, Bob, committee member; Fisk, Nick, committee member; Peersen, Olve, committee member (Colorado State University. Libraries, 2016)
Nucleosome is the basic unit of chromatin and is composed of 147 base pairs of DNA wrapped 1.65 turns around a histone octamer of the four core histones (H2A, H2B, H3 and H4)(Luger et al., 1997). Histones are subject to numerous post-translational modifications. One such modification is the addition of a single ubiquitin (Ub) moiety to a specific lysine residue in the histones, such as H2AK119 or H2BK120 in humans. Depending on the site of Ub attachment, these modifications have distinct functional consequences. Whereas H2A ubiquitination is associated with transcriptional repression and silencing, H2B ubiquitination is associated with actively transcribed regions and has roles in initiation, elongation and mRNA processing. A more recently discovered ubiquitination site in H2A, H2AK13/15, is associated with DNA damage repair. In addition, a number of other ubiquitination sites on all types of histones have been discovered by high throughput mass spectrometry. The functions and regulations of those novel ubiquitinations are not known. Deubiquitinating enzymes (DUBs) reverse these ubiquitinations and therefore, are involved in a variety of regulatory processes. Mutations in several histone DUBs have been implicated in various diseases, thus they represent potential therapeutic targets. The specificity and regulation of histone DUBs are poorly understood in part because it has been difficult to obtain homogenous ubiquitinated histones and nucleosomes to use as substrates in vitro. Previously, several strategies have been developed to produce chemically defined ubiquitinated histones that use a combination of expressed protein ligation (EPL) and solid phase peptide synthesis (SPPS) techniques. These protocols are technically challenging for a biochemical lab. This dissertation describes our successful approach in obtaining homogenous site-specific ubiquitinated H2A and H2B that were then reconstituted into nucleosomes and used to qualitatively and quantitatively characterize a panel of known histone DUBs in vitro. We anticipate that our approach can be applied to generate all types of Ub-histone conjugates regardless of the particular ubiquitination site or histone types. They will significantly facilitate the study of all types of histone ubiquitination.
Keywords: H2A; H2B; ubiquitin; H2AK119Ub; DUBs; H2BK120Ub